A kind of high-dispersion barite powder and preparation method thereof

Through the chemical adsorption and electrostatic effect of betaine dispersant, the problem of barite powder being easily agglomerated in drilling fluid is solved, its dispersion stability and settlement stability are improved, compatibility with organic substrates is enhanced, and the compatibility with the The drilling fluid density is stable.

CN118791034BActive Publication Date: 2024-12-31XUNYANG JIANPING MINING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411124230.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2024-12-31
Estimated Expiration
2044-08-15

AI Technical Summary

Technical Problem

Existing ultrafine barite powder is prone to agglomeration during the dispersion process, resulting in poor dispersion and difficulty in maintaining stability in the drilling fluid, affecting the drilling quality and progress.

Method used

The betaine-type dispersant is used to reduce the surface energy of barite particles through chemical adsorption and electrostatic effects, improve its dispersion stability in the drilling fluid, prevent particles from aggregation through the adsorption layer of polymer molecular chains, and form through ion exchange. Complexes enhance electrostatic stability.

Benefits of technology

It significantly reduces the average particle size of barite powder, improves its dispersion stability and settlement stability in the drilling fluid, enhances compatibility with organic substrates, avoids agglomeration, and improves the density maintenance of the drilling fluid. ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004996093960000051
    Figure BDA0004996093960000051
  • Figure BDA0004996093960000052
    Figure BDA0004996093960000052
  • Figure BDA0004996093960000101
    Figure BDA0004996093960000101
Patent Text Reader

Abstract

The present invention relates to the technical field of inorganic materials, and discloses a highly dispersed barite powder and a preparation method thereof. The cation and anion groups in a betaine-type dispersant can produce strong adsorption and steric hindrance effects on the surface of barite, achieve strong inhibition of polymers, effectively prevent particles from aggregating with each other, reduce the average particle size of the barite powder, increase the electrostatic repulsion between the barites, and effectively improve the dispersion effect of the barites; the carboxylate and sulfonate groups dissociated in the disodium betaine structure can form a complex with barium ions on the surface of barium sulfate particles through ion exchange, generate electrostatic stability and play a role in particle dispersion, and the hydrophilic group with a positive charge at the other end forms an organic shell layer of a certain thickness on the surface of the barite particles, so that the van der Waals force between the particles is weakened, the sedimentation rate and sedimentation volume of the barite powder in the system are reduced, and the dispersion stability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inorganic materials, and in particular to highly dispersed barite powder and a preparation method thereof. Background Art

[0002] Barite is an important type of barium-containing industrial mineral, whose main component is barium sulfate. It has the characteristics of high density, stable chemical and thermodynamic properties, etc. Barite powder is the most important weighting material in petroleum drilling fluid. In order to increase the density of drilling fluid, the usual practice is to use barite for weighting. Since the drilling fluid needs to stay in the well for a long time, barite often settles naturally due to its density, affecting the quality and progress of drilling. To solve this problem, it is necessary to make the barite have better dispersibility and suspension stability in the drilling fluid. The existing preparation of ultrafine barite powder has a small particle size and high surface energy, which makes it easy to agglomerate and has poor dispersibility, thereby limiting the application of ultrafine barite powder. Therefore, the research on barite powder with good dispersibility has become a hot topic of current research.

[0003] The surface of natural barite ore powder is hydrophilic and oleophobic. When used as a filler, it is difficult to disperse evenly in organic materials, thereby affecting the comprehensive performance of the composite material and making it difficult to bring into play the excellent properties of inorganic fillers such as functionality, surface activity and small size. In the prior art, physical dispersion methods are generally adopted, including ultrasonic dispersion, mechanical stirring dispersion, impact dispersion and the like. These physical dispersion methods are all feasible to a certain extent, but once the dispersion is completed and the external environment is restored, the powder particles may re-agglomerate, so that the physical dispersion is subject to certain restrictions. Chemical dispersion is to add a dispersant to the particle suspension so that it is adsorbed on the particle surface, changing the properties of the particle surface, thereby changing the interaction between the particles and the liquid medium, and between the particles, so that the ultrafine powder can be dispersed. In the prior art, the main means to solve the problem of poor dispersibility and easy agglomeration of ultrafine barite powder is to modify the surface of the barite powder. The surface treatment agent selected is usually a fatty acid or a fatty acid salt. Although this method improves the dispersibility of the powder to a certain extent, there are differences in the chemical structure and physical properties of the two. The different surface properties lead to differences in their compatibility and affinity, making it difficult to improve the compatibility of the powder with the organic substrate.

[0004] The present invention prepares a polymer dispersant containing zwitterions and utilizes the chemical adsorption, electrostatic and other effects on the surface of barite to reduce the agglomeration of barite particles due to increased surface energy during the micronization process, improves the compatibility between the two, and improves the dispersion stability of barite powder. Summary of the invention

[0005] The technical problem solved by the present invention is to provide a highly dispersed barite powder and a preparation method thereof, solve the problem that the barite powder is easy to agglomerate during the dispersion process, and improve the dispersion stability.

[0006] The technical solution of the present invention is:

[0007] A method for preparing highly dispersed barite powder is carried out according to the following steps:

[0008] (1) In a nitrogen atmosphere, acrylic acid and deionized water were added to a reaction flask, stirred evenly, and then a solution of the structural formula was added at 40-60°C. N, N'-piperazine-1, 4-bisethylacrylamide betaine and initiator ammonium persulfate are used to carry out polymerization reaction. After the reaction is completed, the pH is adjusted to 6-7 with sodium hydroxide aqueous solution, acetone is added for precipitation, and the betaine type dispersant is obtained after filtering and drying.

[0009] (2) Add barite and deionized water to a reaction flask equipped with a mechanical stirrer, heat to 80-90° C. at 1000-1500 r / min, keep warm for 0.5-1 h, then add a betaine type dispersant and stir for 1-3 h, filter, dry and grind to obtain highly dispersed barite powder.

[0010] Furthermore, in step (1), the ratio of acrylic acid, N,N'-piperazine-1,4-bisethylacrylamide betaine, and ammonium persulfate is 1 mol:(0.9-1.1) mol:(0.04-0.09) mol.

[0011] Furthermore, in step (1), the polymerization reaction temperature is 85-100° C., and the reaction time is 3-6 h.

[0012] Furthermore, the mass fraction of the sodium hydroxide aqueous solution in step (1) is 20-30%.

[0013] Furthermore, in step (2), the ratio of barite to betaine dispersant is 100 g:(0.2-3) g.

[0014] Furthermore, the preparation method of N,N'-piperazine-1,4-bisethylacrylamide betaine in step (1) is carried out according to the following steps:

[0015] Step S1, under a nitrogen atmosphere, add N,N'-di(aminoethyl)-piperazine and tetrahydrofuran to a reaction flask, stir evenly, add potassium carbonate and acryloyl chloride, stir to react, after the reaction is completed, distill under reduced pressure, extract with ethyl acetate and deionized water, concentrate the organic phase, and dry to obtain N,N'-piperazine-1,4-bisethylacrylamide.

[0016] Step S2, under a nitrogen atmosphere, add N,N'-piperazine-1,4-bisethylacrylamide and acetonitrile to a reaction flask, stir evenly, add sodium 2-bromoethane sulfonate, stir to react, after the reaction is completed, cool to room temperature, add ether, precipitate, filter, and recrystallize with ethyl acetate to obtain N,N'-piperazine-1,4-bisethylacrylamide betaine.

[0017] Furthermore, in step S1, the ratio of N,N'-di(aminoethyl)-piperazine, potassium carbonate and acryloyl chloride is 1 mol:(2.1-2.5) mol:(2.05-2.2) mol.

[0018] Furthermore, in step S1, the reaction temperature is 20-35° C., and the reaction time is 5-10 h.

[0019] Furthermore, in step S2, the ratio of N,N'-piperazine-1,4-bisethylacrylamide to sodium 2-bromoethane sulfonate is 1 mol:(2.2-2.4) mol.

[0020] Furthermore, in step S2, the reaction temperature is 70-80° C., and the reaction time is 24-48 h.

[0021] The beneficial technical effects of the present invention are:

[0022] The invention firstly reacts N,N'-di(aminoethyl)-piperazine and acryloyl chloride under the action of potassium carbonate to obtain N,N'-piperazine-1,4-bisethylacrylamide, then quaternizes N,N'-piperazine-1,4-bisethylacrylamide with sodium 2-bromoethane sulfonate to obtain N,N'-piperazine-1,4-bisethylacrylamide betaine, then polymerizes N,N'-piperazine-1,4-bisethylacrylamide betaine with acrylic acid to obtain a betaine type dispersant, and finally disperses and grinds with barite to obtain highly dispersed barite powder.

[0023] The betaine-type dispersant prepared by the present invention has a large molecular weight, and its molecular structure contains cationic and anionic groups that can generate strong adsorption force on the surface of barite, thereby realizing the strong inhibition of the polymer. When adsorbed on the surface of particles, its molecular chain can be fully extended in the medium to form an adsorption layer, and the generated steric hindrance effect can effectively prevent the particles from aggregating with each other, so that the average particle size of the barite powder is effectively reduced; at the same time, the addition of the dispersant significantly increases the surface charge of the barite, increases the absolute value of the surface potential of the particles, increases the electrostatic repulsion between the barites, reduces the attraction between the particles, and effectively improves the dispersion effect of the barite powder.

[0024] The dispersant prepared by the present invention contains a distainine structure. On the one hand, the carboxylate and sulfonate dissociated in the added polymer molecules can form a complex with the barium ions on the surface of the barium sulfate particles through ion exchange, resulting in strong chemical adsorption, and generating electrostatic stability to achieve the effect of particle dispersion; on the other hand, the hydrophilic group with a positive charge at the other end of the polymer dispersant is an organic shell layer of a certain thickness formed on the surface of the barite particles, so that the particles repel each other, the van der Waals force between the particles is weakened, and the particles will not settle rapidly due to the influence of gravity, avoiding the agglomeration of the particles due to the increase of the surface area during the micronization process, achieving the purpose of improving the stable dispersion of the barite powder in the system, and improving the sedimentation stability of the particles, thereby effectively reducing the sedimentation rate and sedimentation volume of the barite powder in the system, so that the dispersion stability of the barite powder is effectively improved. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0026] N,N'-Bis(aminoethyl)-piperazine, CAS number is 6531-38-0.

[0027] Sodium 2-bromoethane sulfonate, CAS number is 4263-52-9.

[0028] Acryloyl chloride, CAS number is 814-68-6.

[0029] Acrylic acid, CAS number is 79-10-7.

[0030] Example 1

[0031] (1) Under nitrogen atmosphere, add 15 mmol of N, N'-di(aminoethyl)-piperazine and 50 mL of tetrahydrofuran to a reaction flask, stir evenly, add 33 mmol of potassium carbonate and 31.5 mmol of acryloyl chloride, react at 25°C for 8 h, distill under reduced pressure, extract with ethyl acetate and deionized water, concentrate the organic phase, and dry to obtain N, N'-piperazine-1,4-diethylacrylamide. The preparation reaction formula is as follows:

[0032]

[0033] (2) Under nitrogen atmosphere, 12 mmol of N, N'-piperazine-1, 4-bisethyl acrylamide and 84 mL of acetonitrile were added to the reaction flask, stirred evenly, and then 27.6 mmol of sodium 2-bromoethane sulfonate was added, reacted at 75°C for 36 h, cooled to room temperature, added with ether, precipitated, filtered, and recrystallized with ethyl acetate to obtain N, N'-piperazine-1, 4-bisethyl acrylamide betaine. The preparation reaction formula is as follows:

[0034]

[0035] (3) Under nitrogen atmosphere, 20 mmol acrylic acid and 80 mL deionized water were added to the reaction flask, and after stirring, 20 mmol N, N'-piperazine-1, 4-bisethylacrylamide betaine and 1.2 mmol initiator ammonium persulfate were added at 50 ° C. The polymerization reaction was carried out at 90 ° C. for 5 h. After the reaction, the pH was adjusted to 7 with a 25% mass fraction of sodium hydroxide aqueous solution, acetone was added for precipitation, and the mixture was filtered and dried to obtain a betaine-type dispersant.

[0036] (4) Add 100 g of barite and 520 mL of deionized water to a reaction flask equipped with a mechanical stirrer, heat to 85° C. at 1300 r / min, keep warm for 1 h, then add 0.2 g of a betaine-type dispersant and stir for 2 h, filter, dry and grind to obtain highly dispersed barite powder.

[0037] Example 2

[0038] (1) Under nitrogen atmosphere, 85 mmol of N,N'-di(aminoethyl)-piperazine and 170 mL of tetrahydrofuran were added to a reaction flask, and after stirring, 178.5 mmol of potassium carbonate and 174.25 mmol of acryloyl chloride were added, and the mixture was reacted at 35°C for 5 h. The mixture was distilled under reduced pressure, extracted with ethyl acetate and deionized water, and the organic phase was concentrated and dried to obtain N,N'-piperazine-1,4-bisethylacrylamide.

[0039] (2) Under a nitrogen atmosphere, 60 mmol of N,N'-piperazine-1,4-bisethylacrylamide and 300 mL of acetonitrile were added to a reaction flask, and after stirring, 132 mmol of sodium 2-bromoethane sulfonate was added, and the mixture was reacted at 80°C for 24 h. The mixture was cooled to room temperature, and ether was added to precipitate. The precipitate was filtered and recrystallized from ethyl acetate to obtain N,N'-piperazine-1,4-bisethylacrylamide betaine.

[0040] (3) Under nitrogen atmosphere, 45 mmol acrylic acid and 135 mL deionized water were added to the reaction flask, and after stirring, 40.5 mmol N, N'-piperazine-1, 4-bisethylacrylamide betaine and 1.8 mmol initiator ammonium persulfate were added at 60 ° C. The polymerization reaction was carried out at 100 ° C. for 3 h. After the reaction, the pH was adjusted to 6 with a 20% sodium hydroxide aqueous solution, acetone was added for precipitation, and the mixture was filtered and dried to obtain a betaine-type dispersant.

[0041] (4) Add 100 g of barite and 500 mL of deionized water to a reaction flask equipped with a mechanical stirrer, heat to 90° C. at 1500 r / min, keep warm for 0.5 h, then add 0.9 g of a betaine-type dispersant and stir for 3 h, filter, dry and grind to obtain highly dispersed barite powder.

[0042] Example 3

[0043] (1) Under nitrogen atmosphere, 50 mmol of N,N'-di(aminoethyl)-piperazine and 250 mL of tetrahydrofuran were added to a reaction flask, and after stirring, 125 mmol of potassium carbonate and 110 mmol of acryloyl chloride were added, and the mixture was reacted at 20°C for 10 h. The mixture was distilled under reduced pressure, extracted with ethyl acetate and deionized water, and the organic phase was concentrated and dried to obtain N,N'-piperazine-1,4-bisethylacrylamide.

[0044] (2) Under a nitrogen atmosphere, 35 mmol of N,N'-piperazine-1,4-bisethylacrylamide and 280 mL of acetonitrile were added to a reaction flask, stirred evenly, and then 84 mmol of sodium 2-bromoethane sulfonate was added. The mixture was reacted at 70°C for 48 h, cooled to room temperature, and ether was added to precipitate. The precipitate was filtered and recrystallized from ethyl acetate to obtain N,N'-piperazine-1,4-bisethylacrylamide betaine.

[0045] (3) Under a nitrogen atmosphere, 100 mmol acrylic acid and 500 mL deionized water were added to a reaction flask, and after stirring, 110 mmol N, N'-piperazine-1, 4-bisethylacrylamide betaine and 9 mmol initiator ammonium persulfate were added at 40 ° C. The polymerization reaction was carried out at 85 ° C. for 6 h. After the reaction, the pH was adjusted to 7 with a 30% sodium hydroxide aqueous solution, acetone was added for precipitation, and the mixture was filtered and dried to obtain a betaine-type dispersant.

[0046] (4) Add 100 g of barite and 600 mL of deionized water to a reaction flask equipped with a mechanical stirrer, heat to 80° C. at 1000 r / min, keep warm for 1 h, then add 1.6 g of a betaine-type dispersant and stir for 3 h, filter, dry and grind to obtain highly dispersed barite powder.

[0047] Example 4

[0048] (1) Under nitrogen atmosphere, 30 mmol of N,N'-di(aminoethyl)-piperazine and 90 mL of tetrahydrofuran were added to a reaction flask, and after stirring, 72 mmol of potassium carbonate and 64.5 mmol of acryloyl chloride were added, and the mixture was reacted at 30°C for 9 h. The mixture was distilled under reduced pressure, extracted with ethyl acetate and deionized water, and the organic phase was concentrated and dried to obtain N,N'-piperazine-1,4-bisethylacrylamide.

[0049] (2) Under a nitrogen atmosphere, 20 mmol of N,N'-piperazine-1,4-bisethylacrylamide and 120 mL of acetonitrile were added to a reaction flask, stirred evenly, and then 47 mmol of sodium 2-bromoethane sulfonate was added. The mixture was reacted at 80°C for 32 h, cooled to room temperature, and ether was added to precipitate. The precipitate was filtered and recrystallized from ethyl acetate to obtain N,N'-piperazine-1,4-bisethylacrylamide betaine.

[0050] (3) Under nitrogen atmosphere, 10 mmol acrylic acid and 35 mL deionized water were added to the reaction flask, and after stirring, 10.5 mmol N, N'-piperazine-1, 4-bisethylacrylamide betaine and 0.6 mmol initiator ammonium persulfate were added at 55 ° C. The polymerization reaction was carried out at 95 ° C. for 5 h. After the reaction, the pH was adjusted to 7 with a 25% sodium hydroxide aqueous solution, acetone was added for precipitation, and the mixture was filtered and dried to obtain a betaine-type dispersant.

[0051] (4) Add 100 g of barite and 550 mL of deionized water to a reaction flask equipped with a mechanical stirrer, heat to 85° C. at 1200 r / min, keep warm for 1 h, then add 2.3 g of a betaine-type dispersant and stir for 3 h, filter, dry and grind to obtain highly dispersed barite powder.

[0052] Example 5

[0053] (1) Under nitrogen atmosphere, 150 mmol of N,N'-di(aminoethyl)-piperazine and 700 mL of tetrahydrofuran were added to a reaction flask, and after stirring, 340 mmol of potassium carbonate and 325 mmol of acryloyl chloride were added, and the mixture was reacted at 35°C for 8 h. The mixture was distilled under reduced pressure, extracted with ethyl acetate and deionized water, and the organic phase was concentrated and dried to obtain N,N'-piperazine-1,4-bisethylacrylamide.

[0054] (2) Under a nitrogen atmosphere, 120 mmol of N,N'-piperazine-1,4-bisethylacrylamide and 840 mL of acetonitrile were added to a reaction flask, stirred evenly, and then 270 mmol of sodium 2-bromoethane sulfonate was added. The mixture was reacted at 80°C for 36 h, cooled to room temperature, and ether was added to precipitate. The precipitate was filtered and recrystallized from ethyl acetate to obtain N,N'-piperazine-1,4-bisethylacrylamide betaine.

[0055] (3) Under a nitrogen atmosphere, 50 mmol acrylic acid and 200 mL deionized water were added to a reaction flask, and after stirring, 48 mmol N, N'-piperazine-1, 4-bisethylacrylamide betaine and 4 mmol initiator ammonium persulfate were added at 45 ° C. The polymerization reaction was carried out at 90 ° C. for 6 h. After the reaction, the pH was adjusted to 6 with a 30% sodium hydroxide aqueous solution, acetone was added for precipitation, and the mixture was filtered and dried to obtain a betaine-type dispersant.

[0056] (4) Add 100 g of barite and 600 mL of deionized water to a reaction flask equipped with a mechanical stirrer, heat to 85° C. at 1500 r / min, keep warm for 0.5 h, then add 3 g of a betaine-type dispersant and stir for 2 h, filter, dry and grind to obtain highly dispersed barite powder.

[0057] Comparative Example 1

[0058] Add 100 g of barite and 520 mL of deionized water into a reaction flask equipped with a mechanical stirrer, heat to 85° C. at 1300 r / min, keep warm for 1 h, filter, and grind to obtain barite powder.

[0059] Comparative Example 2

[0060] (1) Under a nitrogen atmosphere, 20 mmol acrylic acid and 80 mL deionized water were added to a reaction flask, and after stirring, 1.2 mmol initiator ammonium persulfate was added at 50° C., and polymerization was carried out at 90° C. for 5 h. After the reaction, the pH was adjusted to 7 with a 25% sodium hydroxide aqueous solution, acetone was added for precipitation, and the mixture was filtered and dried to obtain a polyacrylic acid dispersant.

[0061] (2) Add 100 g of barite and 520 mL of deionized water to a reaction flask equipped with a mechanical stirrer, heat to 85° C. at 1300 r / min, keep warm for 1 h, then add 0.2 g of polyacrylic acid dispersant and stir for 2 h, filter, dry and grind to obtain barite powder.

[0062] Comparative Example 3

[0063] (1) Under a nitrogen atmosphere, 20 mmol acrylic acid and 80 mL deionized water were added to a reaction flask, and after stirring, 20 mmol N, N'-piperazine-1, 4-bisethylacrylamide (prepared in Example 1) and 1.2 mmol ammonium persulfate as an initiator were added at 50°C, and polymerization was carried out at 90°C for 5 h. After the reaction, the pH was adjusted to 7 with a 25% sodium hydroxide aqueous solution, acetone was added for precipitation, and the mixture was filtered and dried to obtain a polyacrylic acid copolymer dispersant.

[0064] (2) Add 100 g of barite and 520 mL of deionized water to a reaction flask equipped with a mechanical stirrer, heat to 85° C. at 1300 r / min, keep warm for 1 h, then add 0.2 g of polyacrylic acid copolymer dispersant and stir for 2 h, filter, dry and grind to obtain barite powder.

[0065] Particle size test: The average particle size of the prepared barite powder was measured using a laser particle size analyzer.

[0066] Zeta potential test: The prepared barite powder was added into deionized water and oscillated at a constant temperature for 2 h to prepare a suspension with a mass fraction of 10%. The Zeta potential of the surface of the barite particles was tested using a microelectrophoresis instrument.

[0067] Table 1 Average particle size and Zeta potential test

[0068] Average particle size (μm) Zeta potential (mV) Example 1 10.65 -31.6 Example 2 10.17 -37.1 Example 3 7.96 -50.6 Example 4 7.21 -54.2 Example 5 8.18 -51.8 Comparative Example 1 18.27 -5.6 Comparative Example 2 13.75 -20.3 Comparative Example 3 14.90 -17.7

[0069] Barite powder is easy to agglomerate. From the test results in the above table, it can be seen that in Comparative Example 1, no dispersant was added, and the average particle size of the barite reached 18.27 μm. However, with the addition of betaine-type dispersant, the average particle size dropped to 7.21 μm, indicating that the addition of the dispersant effectively dispersed the agglomerated barite, thereby reducing the particle size of the barite powder.

[0070] Zeta potential is a measure of the strength of mutual repulsion or attraction between particles. The smaller the dispersed particles, the higher the absolute value of the Zeta potential and the more stable the system, that is, the dissolution or dispersion can resist aggregation. From the test results in the above table, it can be seen that with the increase of the content of betaine dispersant, the Zeta potential of the barite surface decreases from -5.6mV (negative charge) to -54.2mV, which significantly increases the surface charge of the barite. This is because the molecular structure of the synthetic dispersant contains more sulfonic acid and carboxylic acid groups, which increases the electrostatic repulsion between the barites and effectively improves the dispersion effect of the barite.

[0071] No dispersant was added in Comparative Example 1, and its average particle size was 18.27 μm, the Zeta potential was -5.6 mV, and the dispersion performance was poor; in Comparative Example 2, a polyacrylic acid dispersant was added, and the carboxylate ions in its molecular structure could produce electrostatic effects with the surface groups of barite, and had a certain dispersion effect; in Comparative Example 3, a polyacrylic acid copolymer dispersant was added, and its average particle size was 14.90 μm, and the Zeta potential was -17.7 mV.

[0072] Sedimentation rate test: Take a series of 20mL stoppered sedimentation tubes, weigh 2g of the barite powder prepared in the examples and comparative examples in each sedimentation tube, add 10mL of kerosene, shake, and after the powder is completely wetted, add kerosene to make the volume 20mL. After mixing evenly, shake up and down at a speed of 120 times / min for 3min and then let it stand. Observe and record the change of the powder sedimentation height over time, and calculate the sedimentation rate.

[0073] Sedimentation volume test: After the above-mentioned oscillated sedimentation tube is left to stand for 60 hours, the sedimentation volume of the sample is measured.

[0074] Table 2 Sedimentation rate and sedimentation volume test

[0075]

[0076]

[0077] The sedimentation rate of barite in kerosene can reflect its dispersion degree in kerosene. Natural barite is hydrophilic and oleophobic. It is easy to agglomerate when oscillating in kerosene, and the particles become larger, which will accelerate its sedimentation in kerosene. It can be seen from the test results in the above table that with the increase of the content of betaine dispersant in barite, the sedimentation rate of barite in kerosene gradually decreases. The sedimentation rate in Example 5 is only 0.002 cm 3 / (s·g), indicating that it has good dispersibility in kerosene. This is because the prepared dispersant has a distain structure, which can form a complex through ion exchange, produce strong chemical adsorption, and produce electrostatic stability to achieve the effect of particle dispersion; at the same time, the hydrophilic group with a positive charge at the other end of the polymer dispersant can form an organic shell layer of a certain thickness on the surface of the barite particles, so that the particles repel each other, weaken the van der Waals force between the particles, and will not settle quickly due to the influence of gravity, thereby achieving the purpose of improving the stable dispersion of barite powder in kerosene.

[0078] If the dispersibility of barite in kerosene is good, the barite powder has good wettability in kerosene, the powders are not easy to aggregate, and the particles are arranged and stacked tightly during sedimentation, and the sedimentation volume is small; on the contrary, if the dispersibility of barite in kerosene is poor, the powders are easy to agglomerate, leaving more gaps during sedimentation, and it is easy to form loose sediments, and the sedimentation volume is large; It can be seen from the test results in the above table that after the barite powder was shaken and left to stand for 60 hours in kerosene, the sedimentation volume in Example 5 was only 0.48 cm 3 / g, at this time, the dispersibility and affinity of barite powder in kerosene are better.

[0079] Activation test: 100 mL of deionized water was added to a separatory funnel, and then a mass of m0 of the barite powder prepared by the embodiment and the comparative example was weighed in the separatory funnel. After covering the stopper, it was shaken back and forth at a speed of 120 times / min for 2 min, and then placed on the funnel stand and allowed to stand. After obvious stratification, the lower layer of the material was placed in a crucible filter. After suction filtration, the filtrate was moved into a drying oven and dried to constant weight. The amount of powder m1 obtained was accurately weighed, and the activation degree was calculated as follows: activation degree = (m0-m1) / m0×100%, wherein m0 is the total mass of the barite powder to be tested (g), and m1 is the mass (g) of the powder filtered out after drying to constant weight.

[0080] Table 3 Activation degree test

[0081] Activation degree (%) Example 1 42.6 Example 2 56.2 Example 3 70.5 Example 4 82.3 Example 5 78.7 Comparative Example 1 10.9 Comparative Example 2 36.5 Comparative Example 3 29.2

[0082] Activation degree refers to the dispersion state and surface activity of powder particles. The larger the activation degree, the more uniform the dispersion. It can be seen from the test results in the above table that with the increase in the amount of betaine dispersant used, the activation degree of barite powder gradually increases. The activation degree in Example 4 reaches 82.3%, while the activation degree in Comparative Example 1 is only 10.9%. This is because the betaine dispersant produces electrostatic adsorption on the surface of barite, and its hydrophilic group is adsorbed on the surface of barite while the hydrophobic group is facing outward, which reduces the solubility of barite powder with water, avoids the occurrence of aggregation, and significantly improves the dispersibility of barite powder.

[0083] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing highly dispersed barite powder, characterized in that: The preparation method is carried out according to the following steps: (1) In a nitrogen atmosphere, acrylic acid and deionized water were added to a reaction flask, stirred evenly, and then a solution of the structural formula was added at 40-60°C. N, N'-piperazine-1, 4-bisethylacrylamide betaine and initiator ammonium persulfate are used to carry out polymerization reaction. After the reaction is completed, the pH is adjusted to 6-7 with sodium hydroxide aqueous solution, acetone is added for precipitation, and the betaine type dispersant is obtained after filtering and drying; (2) Add barite and deionized water to a reaction flask equipped with a mechanical stirrer, heat to 80-90° C. at 1000-1500 r / min, keep warm for 0.5-1 h, then add a betaine type dispersant and stir for 1-3 h, filter, dry and grind to obtain highly dispersed barite powder.

2. The method for preparing highly dispersed barite powder according to claim 1, wherein In the step (1), the ratio of acrylic acid, N,N'-piperazine-1,4-bisethylacrylamide betaine, and ammonium persulfate is 1 mol: (0.9-1.1) mol: (0.04-0.09) mol.

3. The method for preparing highly dispersed barite powder according to claim 1, characterized in that, In the step (1), the polymerization reaction temperature is 85-100° C. and the reaction time is 3-6 hours.

4. The method for preparing highly dispersed barite powder according to claim 1, characterized in that The mass fraction of the sodium hydroxide aqueous solution in step (1) is 20-30%.

5. The method for preparing highly dispersed barite powder according to claim 1, characterized in that, In the step (2), the ratio of barite to betaine dispersant is 100 g:(0.2-3) g.

6. The method for preparing highly dispersed barite powder according to claim 1, characterized in that, The preparation method of N,N'-piperazine-1,4-bisethylacrylamide betaine in step (1) is carried out according to the following steps: Step S1, under a nitrogen atmosphere, add N,N'-di(aminoethyl)-piperazine and tetrahydrofuran to a reaction flask, stir evenly, add potassium carbonate and acryloyl chloride, stir to react, after the reaction is completed, perform vacuum distillation, extract with ethyl acetate and deionized water, concentrate the organic phase, and dry to obtain N,N'-piperazine-1,4-bisethylacrylamide; Step S2, under a nitrogen atmosphere, add N,N'-piperazine-1,4-bisethylacrylamide and acetonitrile to a reaction flask, stir evenly, add sodium 2-bromoethane sulfonate, stir to react, after the reaction is completed, cool to room temperature, add ether, precipitate, filter, and recrystallize with ethyl acetate to obtain N,N'-piperazine-1,4-bisethylacrylamide betaine.

7. The method for preparing highly dispersed barite powder according to claim 6, characterized in that, In the step S1, the ratio of N,N'-di(aminoethyl)-piperazine, potassium carbonate and acryloyl chloride is 1 mol:(2.1-2.5) mol:(2.05-2.2) mol.

8. The method for preparing highly dispersed barite powder according to claim 6, characterized in that, In step S1, the reaction temperature is 20-35° C. and the reaction time is 5-10 h.

9. The method for preparing highly dispersed barite powder according to claim 6, characterized in that, In the step S2, the ratio of N,N'-piperazine-1,4-bisethylacrylamide to sodium 2-bromoethane sulfonate is 1 mol:(2.2-2.4) mol.

10. The method for preparing highly dispersed barite powder according to claim 6, characterized in that: In step S2, the reaction temperature is 70-80° C. and the reaction time is 24-48 hours.